Reporting regulation and corporate innovation - Matthias Breuer; Christian Leuz; Steven Vanhaverbeke (Goethe University Frankfurt, Center for Financial Studies (CFS), 2021)
We investigate the impact of reporting regulation on corporate innovation. Exploiting thresholds in Europe's regulation and a major enforcement reform in Germany, we find that forcing firms to publicly disclose their financial statements discourages innovative activities. Our evidence suggests that reporting regulation has significant real effects by imposing proprietary costs on innovative firms, which in turn diminish their incentives to innovate. At the industry level, positive information spillovers (e.g., to competitors, suppliers, and customers) appear insufficient to compensate the negative direct effect on the prevalence of innovative activity. The spillovers instead appear to concentrate innovation among a few large firms in a given industry. Thus, financial reporting regulation has important aggregate and distributional effects on corporate innovation.
Keywords: K22; L51; M41; M42; M48; O43; O47; 330; Innovation; Regulation; Disclosure; Financial Reporting; Patents; Growth